HUBUNGAN KEMOTERAPI DAN ASUPAN ENERGI DENGAN STATUS GIZI PASIEN KANKER PAYUDARA STADIUM II DAN III DI RSUP FATMAWATI JAKARTA PADA TAHUN 2018-2019 Relationship of Chemotherapy and Energy Intake with Nutritional Status of Breast Cancer Patients Stage II-III at Fatmawati General Hospital in 2018–2019 - Alfat Hidayat; Luh Eka Purwani; Nunuk Nugrohowati (Media Gizi Indonesia, 2020)
Breast cancer is the highest cause of death in women around the world. Common problems that arise in breast cancer patients is nutritional problems. The purpose of this study was to determine the relationship between chemotherapy, energy intake and nutritional status of stage II and III breast cancer patients at Fatmawati General Hospital in 2018-2019. The type of study was observational analytic with cross-sectional design on 34 breast cancer patients at Fatmawati General Hospital. The sample used purposive sampling technique by choosing patients who accomplish inclusion criterias including patients with compos mentis state, stage II and III, aged between 25–64 years old, have been taken chemotherapy without complication, outpatient, and agreed to be participant in this study. The exclusion criteria were patients with undernutrition before chemotherapy, received radiation and hormonal therapy, patients with severe infectious diseases (TBC and HIV/AIDS) and chronic diseases. The taken datas including nutritional status measured by Body Mass Index (BMI); chemotherapy status gained from medical record; and energy intake assessed by 3×24 hours food recall. The Chi-Square test showed there was no relationship between chemotherapy and nutritional status of breast cancer patients (p=1.000). However, there was a relationship between energy intake and nutritional status of breast cancer patients (p<0.05) with CI 95%, OR = 65.000 (4.905-861.448) which means that the patients with the intake of energy defi cit have 65 times bigger risk for malnutrition. The conclusion from this study is, there was a relationship between the energy intake with nutritional status of stage II and III breast cancer patients at Fatmawati General Hospital.